2005
DOI: 10.1080/00071660500066258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feeding time on shell quality and oviposition time in broiler breeders

Abstract: Three experiments were performed to determine the effect of feeding time on shell quality and oviposition time in broiler breeders. Mean eggshell thickness was increased significantly by 3.5 microm (approximately 1%) per h delay in feeding time when hens were housed in individual cages. However, eggshell thickness was not significantly affected by feeding time when birds were housed on litter floors. Mean oviposition time was delayed relative to lights on by 5 min per h delay in feeding time. Egg weight was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 14 publications
4
22
0
1
Order By: Relevance
“…Moreover, Samara et al (1996) and Harms (1991) reported that egg weight was not affected by feeding time. In addition, Backhouse and Gous (2005) report that egg weight was not significantly affected by the feeding time, suggesting that differences in shell thickness and oviposition times were not due to increased oviducal transit times.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, Samara et al (1996) and Harms (1991) reported that egg weight was not affected by feeding time. In addition, Backhouse and Gous (2005) report that egg weight was not significantly affected by the feeding time, suggesting that differences in shell thickness and oviposition times were not due to increased oviducal transit times.…”
Section: Discussionmentioning
confidence: 93%
“…The results of this study were according to the results reported by Cave (1981), Bootwalla et al (1983) and Samara et al (1996), who reported that different feeding schedules had no effect on egg production. Backhouse and Gous (2005) evaluated different feeding schedules for broiler breeders (57 week old), at 07:30 AM, 10:00 AM, 1:00 PM and 3:30 PM and other treatments, in which hens were daily half fed at 07:30 AM and at 3:30 PM (half-feeding) and it was observed that feeding time had no significant effect on total egg production from 26 to 32 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clutch length is an external indicator of the ovarian follicular growth in the rapid growth phase (Bahr and Palmer, 1989;Johnson, 1999;Zakaria, 1999aZakaria, , 2001Johnston and Gous, 2003). Oviposition time has been influenced by strain (Lewis et al, 2004;Campo et al, 2007;Tumova and Gous, 2012), lighting schedule (Lewis et al, 2001(Lewis et al, , 2004 and feeding time (Backhouse and Gous, 2005) of a flock. However, data about egg laying pattern of feed restricted broiler breeders are relatively limited.…”
Section: Introductionmentioning
confidence: 98%